L’évaluation de la durabilité des fruitières à comté : vers un nouvel outil de management ? - Philippe Jeanneaux (Développement Durable et Territoires)
Sustainability assessment at the PDO comté cooperatives level: towards a new tool for management? The Jura region is based on a local organization between farming sector and industry. Numerous small cooperatives (the fruitières, which produce young cheese) are now threatened by the merger movement of the sector and they wonder about their future. We develop a method to assess the sustainability of these firms constructed around 60 indicators. We put to the test 15 cooperatives. We show their position depends not only on economical performances, but also on social, territorial and environmental features. We assume that the stake for the perenniality of the cooperatives is to take the sustainable principles into account in their management.